2016
DOI: 10.1161/jaha.116.003226
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Computed Tomography (CT) Angiography as a Predictor of Cardiac and Noncardiac Vascular Events in Asymptomatic Type 2 Diabetics: A 7‐Year Population‐Based Cohort Study

Abstract: BackgroundType 2 diabetics are at increased risk for vascular events, but the value of further risk stratification for coronary heart disease (CHD) in asymptomatic subjects is unclear. We examined the added value of coronary computed tomography angiography over clinical risk scores (United Kingdom Prospective Diabetes Study), and coronary artery calcium in a population‐based cohort of asymptomatic type 2 diabetics.Methods and ResultsSubjects (n=630) underwent baseline clinical assessment and computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…One year later, a study of 630 diabetic subjects without known CAD underlined that a combination of CCTA with clinical risk stratification methods and coronary artery calcium score is effective in detecting patients with greater risk of primary cardiovascular events (Table II) (41).…”
Section: Imaging Methods As Predictors For Cadmentioning
confidence: 99%
“…One year later, a study of 630 diabetic subjects without known CAD underlined that a combination of CCTA with clinical risk stratification methods and coronary artery calcium score is effective in detecting patients with greater risk of primary cardiovascular events (Table II) (41).…”
Section: Imaging Methods As Predictors For Cadmentioning
confidence: 99%
“…Eligible subjects had type 2 diabetes mellitus, were aged 55-74 years, had no history of CAD or HF, but had at least 1 additional cardiovascular (CV) risk factor [10]. The study was approved by the hospital Ethics Committee and all subjects provided written informed consent before inclusion in study procedures.…”
Section: Methodsmentioning
confidence: 99%
“…CTA was performed between October 2006 and October 2008 with a 64-slice scanner (Brilliance CT, Philips Healthcare, Cleveland, OH, USA) using a spiral, retrospective, ECG-gated protocol as previously described [10]. Beta-blockers and sublingual nitrates were used routinely.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, another publication by the same study group refers to a previous study in the same patient cohort where maximal treadmill exercise was studied in diabetic patients [10]. It was shown that the maximal exercise level was not an independent predictor of coronary heart disease outcome events.…”
mentioning
confidence: 99%